Transformasi Manajemen Sumber Daya Manusia dalam Menghadapi Industri 5.0: Kajian Literatur Sistematis - Westri Andayanti (Indo Publishing, 2025)
This study aims to analyze the transformation of human resource management (HRM) in facing the Industry 5.0 era through a systematic literature review approach. Industry 5.0 represents a paradigm shift from automation toward collaboration between humans and intelligent technologies within a human-centric framework. Based on an extensive review of scholarly literature indexed in Google Scholar and Mendeley from 2019 to 2024, the findings indicate that digital HR transformation requires organizations to adapt through the integration of AI, big data, and IoT technologies in recruitment, career development, and performance evaluation processes. Moreover, transformational leadership and innovative organizational culture play vital roles in ensuring the success of this transformation. The results also highlight that the success of HRM in the Industry 5.0 era is determined not only by technological capabilities but also by the organization’s ability to balance productivity, employee well-being, and digital ethics. This research contributes both theoretically and practically to the development of an adaptive, humanistic, and sustainable HRM model that supports organizational competitiveness in the Industry 5.0 era..